Examining the role of digitalization and gig economy in achieving a low carbon society: an empirical study across nations - Liu, Kai; Feng, Zerong; Zhang, Qihang (Frontiers in Environmental Science, 2023)
This paper examines the international relationship between digitalization, the gig economy, and low carbon development. Using a large dataset of countries with varying degrees of digitalization and prevalence of the gig economy, the study demonstrates that the impact of digitalization on the gig economy varies by income level, with a positive relationship in high-income countries and a negative relationship in low-income countries. The results also indicate that the gig economy has a significant negative impact on greenhouse gas emissions, particularly CO2 emissions, suggesting that its growth may support the reduction of emissions and the transition to a low-carbon society. In addition, the gig economy mediates the connection between digitalization and low-carbon development. These findings have significant policy implications for governments and stakeholders attempting to advance sustainable development and a low-carbon society. Additionally, the study identifies areas for future research, such as examining the heterogeneous effects across income levels, sectoral differences in the gig economy, and the dynamic nature of the gig economy and digitalization.